URBAN INDUSTRIAL ENTERPRISES’ EMISSIONS OF HARMFUL SUBSTANCES AND THEIR ECOLOGICAL MONITORING INDICATORS - Mirsagatova M. R.; Jalolov N. N. (American Journals Publishing, 2025)
The article examines the negative impacts of industrial facilities in urban areas on air, water, and soil as the main sources of pollutant emissions, as well as key ecological indicators used to monitor these processes. Scientific research shows that industrial emissions release harmful chemical substances — including heavy metals, volatile compounds, and organic contaminants — into the environment, posing risks to human health and ecosystem integrity. The article outlines methodological foundations of ecological monitoring, analyzes pollution levels through monitoring indicators and their results, and proposes sustainable management measures.
Keywords: Industrial emissions, ecological monitoring, air pollution, water quality, soil contamination